Pancarta relacionada con las protestas situada en la fachada principal de la Iglesia de Nuestra Señora de Fátima - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Pancarta relacionada con la huelga nacional indefinida colocada en la fachada principal de la Iglesia de Nuestra Señora de Fátima, Iquitos.
ENGLISH: Banner related to the indefinite national strike placed on the main facade of the Church of Our Lady of Fatima, Iquitos.

SPANISH: Pancarta relacionada con la huelga nacional indefinida colocada en la fachada principal de la Iglesia de Nuestra Señora de Fátima, Iquitos.
ENGLISH: Banner related to the indefinite national strike placed on the main facade of the Church of Our Lady of Fatima, Iquitos.
Banner related to the protests located on the main façade of the Church of Our Lady of Fatima
Keywords: Social events|~|Iquitos (Perú)|~|Catholic Institutions|~|Catholic schools|~|Catholic priests|~|Acontecimientos sociales|~|Iquitos (Perú)|~|Instituciones Católicas|~|Escuelas Católicas|~|Sacedote Católica